[OP.4C.06] SLEEP TO LOWER ELEVATED BLOOD PRESSURE: A RANDOMISED CONTROLLED TRIAL (SLEPT). (September 2016) - McGrath, E.; Espie, C.; Power, A.; Murphy, A.; Newell, J.; Kelly, C.; Duffy, N.; Gunning, P.; Gibson, I.; O'Donnell, M.
Abstract : Objective: Impaired sleep quality is common, and is associated with an increased risk of cardiovascular disease and death, thought to be mediated by adverse effects on established vascular risk factors, particularly hypertension. The aim of this study was to determine if a web-delivered sleep intervention reduces blood pressure compared to vascular risk factor education alone (standard care), through modification of sleep quality. Design and method: Design/setting/participants: A Phase II, proof-of-concept, randomised, blinded controlled trial of 134 community-based participants with sleep impairment and systolic blood pressure (130–160 mmHg) and diastolic blood pressure (<110 mmHg) without cardiovascular disease. Intervention: Multi-component web-delivered sleep intervention Sleepio™ (sleep hygiene education, stimulus control and cognitive behavioural therapy) delivered over 8 weeks in addition to standard care (n = 67), compared to standard care alone (n = 67). Main Outcome Measures: Difference in the mean change in 24-hour ambulatory systolic blood pressure (SBP) over 8 weeks between intervention and control groups. Secondary outcomes included mean change in measures of sleep quality and psychosocial health, including the Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Results: Participants in the sleep intervention group showed significantly greater improvements in sleep quality (PSQI, 2.5 vs. 1.4, P = 0.04; ISI, 4.5 vs. 1.7, P < 0.001; sleep efficiency, 5.0 vs.0.5, P = 0.02) and psychosocial health (BDI, 2.5 vs. 0.5, P = 0.02; BAI, 2.2 vs. 0.8; P = 0.047) compared to control participants. Mean change in 24 hour ambulatory SBP over 8 weeks was not significantly different between the sleep intervention (0.9 mmHg) and control (0.8 mmHg) arms, difference 0.1 (95% CI −3.4 to 3.2). Conclusions: A simple, low-cost, web-delivered sleep intervention significantly improves sleep quality and measures of psychosocial health, but does not result in short term improvements in blood pressure. Trial Registration: ClinicalTrials.gov identifier: NCT01809821